Legal Protection For Victims Of Traffic Violations That Lead To Death (Case Study On Police Traffic of Rembang) - Hengki Irawan; Sri Endah Wahyuningsih; Jawade Hafidz (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2019)
The purpose of this study is to know, shortly describe, analyze and assess the implementation, barriers, and the remedies to overcome obstacles in the legal protection for victims of traffic abuses resulting in death by Police Traffic of Rembang. The method used in this study, using a kind of sociological juridical research, analytical, descriptive, with data used are primary data and secondary data, and analyzed Qualitative. The results of this study are: (1) legal protection for victims of traffic abuses resulting in death by Police Traffic of Rembang preferably through peace settlement with restitution, (2) barriers in the legal protection for victims of terms: (a) the substance of the law: Act No.22 of 2009 and the Criminal Procedure Code has not been providing legal protection for victims and their families; (B) the legal structure: lack of personnel and infrastructure; and (c) the legal culture: the lack of public awareness; (3) the remedies to overcome these obstacles, in terms of: (a) the substantive law: consideration of material and immaterial damages the victim or the victim's family, (b) the legal structure: additional personnel and high-tech infrastructure, human resource development; and (c) legal cultures: socialization and education traffic rules, and concept of restorative justice. (A) the substantive law: consideration of material and immaterial damages the victim or the victim's family, (b) the legal structure: additional personnel and high-tech infrastructure, human resource development; and (c) legal cultures: socialization and education traffic rules, and concept of restorative justice. (A) the substantive law: consideration of material and immaterial damages the victim or the victim's family, (b) the legal structure: additional personnel and high-tech infrastructure, human resource development; and (c) legal cultures: socialization and education traffic rules, and concept of restorative justice.Keywords: Death; Victim; Traffic; Abuse; Legal Protection.